The Role of G5 Sahel States in German Political-Military Strategy in Africa - Ph. O. Trunov (Контуры глобальных трансформаций: политика, экономика, право, 2020)
The article raises the question of whether German participation in resolving the armed conflict in Mali is a special case or, on the contrary, is a transition to a new political‑military strategy in Africa. In this regard the author issues the key parameters of Bundeswehr`s usage in Africa from 1990‑s until the middle 2010‑s and pays special attention to Somalia. The paper analyzes the features of German military presence evolution there. In comparison with Somalian one the author explores German approach to the resolution of the Malian armed conflict at the period of 2013‑2015 and since 2016. The paper pays attention to the Bundeswehr`s usage in EUTM Mali and MINUSMA missions and the results of this process. The article underlines the huge increase of German military presence since 2016‑2018 in Mali and shows the reasons of this tendency. Considering German activity in Mali, the paper explores its «spillover effect» with the examples of German relations with Algeria and G5 Sahel countries. In this regard the scientific research pays special attention to German bilateral relations with Burkina‑Faso and Niger. The paper underlines that by the beginning of the 2020‑s FRG concentrated its efforts in the African states which belong to traditional sphere of French interests. In the conclusion the author shows the importance of Sahel region for the testing of new German politicalmilitary strategy in Africa.